Orthopedic treatment in a patient with maxillary deficiency: a case report (Research, Society and Development, 2021)
Objective: The aim of this article is to describe a clinical case of orthodontic and orthopedic treatment of a nine-year-old child, Angle Class III, using a face mask. Methodology: Based on the patient's permission through the Free and Informed Consent Form to share her image for the proper purpose, this study is a clinical case report of descriptive analytical nature (Pereira et al., 2018). Case Report: Patient I. A. C, 9 years old, female, white, attended the dental clinic of Centro Universitário Fametro (CEUNI-FAMETRO) accompanied by her mother, complaining about the “shame of smiling”. After signing the Informed Consent Form (FICF), an anamnesis was carried out, in which the guardian reported the child's good health and mouth breathing habits. Final Considerations: Given the above, it can be stated that the results of the treatment of skeletal discrepancy due to maxillary deficiency were not achieved. In the present case report, the patient was uncooperative, which culminated in changing the circuit breaker due to the child having broken the device twice.